2010
DOI: 10.1177/197140091002300308
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Image Analysis of the Temporal Bone in Patients with Unilateral Attic Cholesteatoma

Abstract: We determined temporal bone anatomy in patients with unilateral attic cholesteatoma. We compared the affected and normal ears of ten patients with unilateral attic cholesteatoma using three-dimensionally reconstructed high-resolution computed tomography images of the temporal bone. We determined the eustachian tube angle, eustachian tube length, sizes of the tympanic orifice of the eustachian tube, the pars flaccida, and the mastoid cavity, and distances of the pars flaccida and the tympanic orifice of the eus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The imaging findings associated with ETD have not been extensively described, with only six published papers identified as describing features detectable on imaging that are suggestive of ETD [ 12 , 24 , 32 , 40 42 ]. All except one [ 24 ] are based on CT findings (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The imaging findings associated with ETD have not been extensively described, with only six published papers identified as describing features detectable on imaging that are suggestive of ETD [ 12 , 24 , 32 , 40 42 ]. All except one [ 24 ] are based on CT findings (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two groups found that the bony channel for the Eustachian tube within the temporal bone was of reduced cross sectional size in individuals with obstructive ETD [ 12 , 40 ], and one group found that the tube ran at a shallower angle in diseased ears [ 42 ]. Kanzaki et al highlight one of the weaknesses of using CT to assess soft tissues; as by scanning pre- and post-grommet insertion, they demonstrated that mucus and fluid cannot easily be distinguished from soft tissue obstructing the lumen [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The three arms have been selected to reflect the variation in current practice, with all interventions already in widespread clinical use. Oral steroid (prednisolone) is included as an intervention as this is recommended in guidelines [ 16 ], and used by most ENT clinicians across the UK [ 23 , 24 ]. As the current standard of care, this represents the control intervention.…”
Section: Discussionmentioning
confidence: 99%
“… American Academy of Otolaryngology–Head & Neck Surgery hearing recovery criteria [ 16 ]. Classification shown with the associated audiometric criteria.…”
Section: Methodsmentioning
confidence: 99%
“…A few studies have indicated that acquired cholesteatoma is associated with bone formation and absorption, but most of these studies are case reports, animal tests, or cytology studies [ 3 5 ]. A previous study indicated that acquired cholesteatoma is associated with anatomical abnormalities or other bone diseases such as osteoporosis [ 9 ]. However, no large-scale epidemiological study has been conducted to investigate this association.…”
Section: Introductionmentioning
confidence: 99%